Wild tomato endosperm transcriptomes reveal common roles of genomic imprinting in both nuclear and cellular endosperm. (29th July 2018) - Roth, Morgane; Florez‐Rueda, Ana M.; Paris, Margot; Städler, Thomas
Summary: Genomic imprinting is a conspicuous feature of the endosperm, a triploid tissue nurturing the embryo and synchronizing angiosperm seed development. An unknown subset of imprinted genes (IGs) is critical for successful seed development and should have highly conserved functions. Recent genome‐wide studies have found limited conservation of IGs among distantly related species, but there is a paucity of data from closely related lineages. Moreover, most studies focused on model plants with nuclear endosperm development, and comparisons with properties of IGs in cellular‐type endosperm development are lacking. Using laser‐assisted microdissection, we characterized parent‐specific expression in the cellular endosperm of three wild tomato lineages (Solanum section Lycopersicon). We identified 1025 candidate IGs and 167 with putative homologs previously identified as imprinted in distantly related taxa with nuclear‐type endosperm. Forty‐two maternally expressed genes (MEGs) and 17 paternally expressed genes (PEGs) exhibited conserved imprinting status across all three lineages, but differences in power to assess imprinted expression imply that the actual degree of conservation might be higher than that directly estimated (20.7% for PEGs and 10.4% for MEGs). Regardless, the level of shared imprinting status was higher for PEGs than for MEGs, indicating dissimilar evolutionary trajectories. Expression‐level data suggest distinct epigenetic modulation of MEGs and PEGs, and gene ontology analyses revealed MEGs and PEGs to be enriched for different functions. Importantly, our data provide evidence that MEGs and PEGs interact in modulating both gene expression and the endosperm cell cycle, and uncovered conserved cellular functions of IGs uniting taxa with cellular‐ and nuclear‐type endosperm. Significance Statement: The biological functions of parent‐of‐origin–dependent gene expression in the endosperm during early seed development have remained largely elusive, partly because previous studies focused on just one developmental type of endosperm. Using laser‐assisted microdissection of the cellular endosperm in three closely related species of wild tomatoes, we present a comparative study of genomic imprinting, revealing apparently conserved cellular functions of imprinted genes that unite taxa with cellular‐ and nuclear‐type endosperm.